2017
DOI: 10.1177/0961203317735186
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical gray matter atrophy is associated with cognitive deficit in multiple sclerosis but not in systemic lupus erythematosus patients

Abstract: Cognitive impairment is a significant clinical problem both in multiple sclerosis (MS) and systemic lupus erythematosus (SLE) patients. In MS cognitive dysfunction has been associated with brain atrophy and total demyelinating lesion volume. In SLE cognitive impairment is much less understood, and its link to structural brain damage remains to be established. The aim of this study was to identify the relationship between subcortical gray matter volume and cognitive impairment in MS and SLE. We recruited 37 MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…27 Only a limited number of studies have previously focused on the association between cognitive function and brain volumes on MRI in patients with SLE without major nervous system involvement ('non-NPSLE'). [28][29][30][31][32][33][34][35][36][37] Several studies found an association between global cognitive impairment and reduced grey matter 36 or white matter volume 28 30 36 and in one study this association was not found. 31 In our study, we demonstrated that brain volumes were indeed associated with cognitive function (all domains) in patients with SLE, but differences were present between NPSLE phenotypes.…”
Section: Lupus Lupus Lupusmentioning
confidence: 96%
“…27 Only a limited number of studies have previously focused on the association between cognitive function and brain volumes on MRI in patients with SLE without major nervous system involvement ('non-NPSLE'). [28][29][30][31][32][33][34][35][36][37] Several studies found an association between global cognitive impairment and reduced grey matter 36 or white matter volume 28 30 36 and in one study this association was not found. 31 In our study, we demonstrated that brain volumes were indeed associated with cognitive function (all domains) in patients with SLE, but differences were present between NPSLE phenotypes.…”
Section: Lupus Lupus Lupusmentioning
confidence: 96%
“…In fact, all patients were assessed for cognitive impairment with a battery of neuropsychological tests, as published in our previous manuscript. 35 It has to be noted that although the SLEDAI score of our SLE group was relatively high, this was caused by the fact that they were all defined as NPSLE, so they were arbitrarily added eight points, even if NP symptomatology was headache or mild cognitive impairment. Those symptoms do not necessarily reflect high disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, all patients were assessed for cognitive impairment with a battery of neuropsychological tests, as published in our previous manuscript. 35…”
Section: Discussionmentioning
confidence: 99%
“…En relación a las medidas de volumen general, nuestro estudio encontró asociación moderada únicamente con el test PASAT (tiempo y aciertos). Coincidentes con estudios previos como el de Kalinowska-Lyszczarz [26] o Lazeron [27], los resultados obtenidos subrayan la sensibilidad de este test en la valoración de las funciones ejecutivas en EM, mostrando consonancia con estudios que incluso llegan a proponerlo como el test con mayor sensibilidad en la medida del cociente intelectual en este tipo de población [28].…”
Section: Discussionunclassified